THE ECONOMIC VALUATION OF AREN (Arenga pinnata MERR) AT KIYAP JAYA VILLAGE BANDAR SEIKIJANG DISTRICT PELALAWAN REGENCY RIAU PROVINCE - Morina Widya Afifa; Yossi Oktorini; Mukhamadun (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2022)
Aren (Arenga pinnata Merr) was one of the non-wood forest products that could be used start from sap, fruit, palm fiber, stems, leaves, and roots. Almost all products have economic value. This research was to study the benefits and have the economic values in Kiyap Jaya Village, Bandar Sei Kijang District, Pelalawan Regency, Riau Province. This research used a qualitative descriptive method by using economic analysis by asking for market prices and obtaining productivity. The sugar palm parts that are truly utilized by the community are roomie, fruit, and roots. As for the fibers, the stems and leaves has not been maximally utilized. The sap was used as an alternative medicine for diabetes mellitus and kidney failure. The Fruit was useful as a mixture of food and roots that are used as a tonic and urinary stones. The total economic value in the Kiyap Jaya Village was Rp. 31,450,000 per stem in one year, which was the highest economic value in the room of Rp. 25,550,000 per-month.